Strategi Manajemen Pembiayaan Kesehatan dan Asuransi dalam Pelayanan Kesehatan: Studi Literature - Yuliarti Pasau; Vip Paramarta (STIKes Ibnu Sina Ajibarang, 2023)
Health is a vital element and is a constitutive element in a person's life process. So that improving health, health recovery and treatment cannot be separated from financing. One of the subsystems in national health is the health financing subsystem. Health financing itself is the amount of funds that must be provided to organize and/or utilize various health efforts needed by individuals, families, groups and communities. The aim of this research is to find out the management strategy for health financing and insurance in health services. The method used is a literature study by analyzing and comparing existing theories and producing findings from the analysis results. The results of this research are strategies for managing health financing and insurance in health services, namely by providing health services, increasing health personnel, improving information, providing adequate health equipment, vaccines and technology, good leadership and governance in management and financing and accelerating access to health services as a whole. universal for reducing inequalities in health. It can be concluded that strong, stable and sustainable health financing plays a very vital role in the provision of health services in order to achieve various important goals of health development in a country, including equal distribution of health services and access (equitable access to health care) and quality services (guaranteed quality). Therefore, health policy reform in a country should provide an important focus on health financing policies to ensure the implementation of adequacy, equity, efficiency and effectiveness of health financing itself.